In situ construction of 3-dimensional hierarchical carbon nanostructure; investigation of the synthesis parameters and hydrogen evolution reaction performance. (30th June 2021) - Alali, Khaled Tawfik; Jing yu; Moharram, Deema; Liu, Qi; Chen, Rongrong; Zhu, Jiahui; Li, Rumin; Liu, Peili; Liu, Jingyuan; Wang, Jun
Abstract: Hierarchical 3-dimensional (3D) carbon nanostructures have potential applicability in several electrochemical energy applications own to their sizeable effective surface, specific energy density, cycling stability and flexibility. Herein, combining electrospinning with in situ chemical vapor deposition (CVD) technologies as an efficient and secure procedure is applied for constructing 3D carbon nanostructure-based on carbon fibers (CFs) and electrospun carbon nanofibers (ECNFs). Affect the catalysis type, immersion solution, carbon sources and treat temperature are experimentally demonstrated. Cactus-like 3D carbon nanomaterials are constructed via growth forest-like carbon nanofibers (CNFs) directly on both CNFs and CFs at 900 °C using Ni as a catalyst, cellulose acetate (CA) as carbon source and ethanol-urea as an immersions solution. The Ni/CNFs/ECNFs mat exhibits a large surface area of 342.3 m 2 g −1, while just 19.3 m 2 g −1 is recorded to Ni/CNFs/CFs. Based on the nano-nonwoven structure and forest-like grown CNFs nanostructure, Ni/CNFs/ECNFs exhibit a favorable hydrogen evolution reaction (HER) performance in an alkaline medium with a low overpotential of 88 mV to deliver 10 mV cm −2 current density and Tafel slope of 170 mV dec −1 . This work proves the synthesis parameters of 3D hierarchical carbon nanostructures and their enticing to apply as an advanced substrate for electrochemical applications. Graphical abstract: Image 1 Highlights: Constructing 3D-hierarchical carbon nanostructure by combining electrospinning and pyrolysis technologies. Propose a secure and efficient in situ CVD technology for growing CNFs layer on electrospun CNFs and commercial CFs. Investigate the effect of the growth temperature, carbon sources, immersion solution and catalysis type. Flexible Ni/grown CNFs/electrospun CNFs nanomaterial offers a large active surface area. 3D hierarchical carbon nanostructure is an advanced substrate for electrochemical applications.